Pengaruh Kepemimpinan dan Motivasi terhadap Kinerja Guru SMAN 30 Kabupaten Tangerang - Lilis Nurul Husna (Universitas Tangerang Raya, 2022)
The purpose of this study was to analyze the effect of leadership style and motivation on teacher performance at SMAN 30 Tangerang Regency. The success of an organization is determined by the performance of teachers in operating the work units in the agency. Teacher performance can be influenced by several factors, including leadership style and motivation. The object of this research is the teacher of SMAN 30 Tangerang Regency. The samples used were all teachers of SMAN 30 Tangerang Regency as many as 20 respondents. The analysis used is multiple linear regression. The results of the regression analysis between leadership style and motivation on performance obtained positive results of Y = a + b1X1 + b2X2 = 14,699 + 0,468 + 0,553. The results of hypothesis testing using t-test showed significant results with a significance of 0.046 and 0.041 < =0.05. Based on the results of the analysis, it can be concluded that leadership style and motivation have a positive and significant effect on teacher performance. Keywords— Leadership Style, Motivation, Teacher Performance.